ETHICS AND KNOWLEDGE OF RECURSIVITY IN PSYCHOLOGISTS TRAINING - Ramón Sanz Ferramola (CAEN, 2008)
This work deals with the characterization of psychology as a science and profession. Thisfeature is part of the Argentine academic tradition which goes from the origins of psychology as an undergraduate program by the end of the 1950s to the present day. In relation to this topic, four issues are analysed: a) the knowledges of psychology showing the necessity of two epistemic dimensions closely related, namely the discursivity and recursivity, or knowledge and metaknowledge, b) the role of psychology as a profession within the praxis, rather than in the poiesis, according to the Greek distinction between the implications of these two modalities of the "doing", c) the concurrence and difference of ethics and deontology, their roles, bounds and potentialities within the psychological field in general, and that of scientific-professional morality in particular, and d) the definition and characterization of ethics and epistemology as knowledge of recursivity in psychologists' training.